Investigation of M-Learning Components and the Vital Features that affects the Design, and Deployment of M-Learning Process Workflows - Okoro Barnabas Udo; Tombari Tete (International Journal on Human-Computing Studies, 2022)
Mobile learning (m-learning) allows learners to access services from anywhere irrespective of time using internet-enabled mobile gadgets and related technologies. To assess the extent to which m-learning workflows have affected the learning process, it is imperative to evaluate the components and features of mobile learning and the level of interactions between the various components. The aim of this paper is to investigate m-learning components and the vital features that affect the design, development and deployment of m-learning process workflows. The paper follows a systematic review augmented by the object-oriented analysis and design process modeling. Following the process workflows modeling, the paper evolves and discusses an implementation-ready model that could be adopted by m-learning system integrators in their bid to implement cutting edge mobile solutions for flexible and efficient e-learning